Peripheral Endogenous Cannabinoid Levels Are Increased in Schizophrenia Patients Evaluated in a Psychiatric Emergency Setting - Potvin, Stéphane; Mahrouche, Louiza; Assaf, Roxane; Chicoine, Marjolaine; Giguère, Charles-Édouard; Furtos, Alexandra; Godbout, Roger (Frontiers in Psychiatry, 2020)
Background The endogenous cannabinoid system mediates the psychoactive effects of cannabis in the brain. It has been argued that this system may play a key role in the pathophysiology of schizophrenia. While some studies have consistently shown that the levels of anandamide, an endogenous cannabinoid ligand, are increased in the cerebrospinal fluid of schizophrenia patients, inconsistent results have been observed in studies measuring anandamide levels in the periphery. Here, we sought to determine if the assessment of peripheral anandamide levels in patients evaluated in a psychiatric emergency setting would show robust increases. Methods One hundred seven patients with a schizophrenia-spectrum disorder from the psychiatric emergency settings of the Institut Universitaire en Santé Mentale de Montréal and 36 healthy volunteers were included in the study. A subsample of thirty patients were assessed at two time points: at the emergency and at their discharge from the hospital. Anxious and depressive symptoms, sleep and substance use were assessed using self-report questionnaires. In addition to anandamide, the levels of oleoylethanolamide (OEA), an anorexigenic fatty-acid ethanolamide, were also measured, since the prevalence of the metabolic syndrome is increased in schizophrenia. Plasma levels of anandamide and OEA were measured using liquid chromatography and mass spectrometry. Results Plasma anandamide and OEA levels were significantly increased in schizophrenia patients, relative to controls (Cohen’s d=1.0 and 0.5, respectively). Between-group differences remained significant after controlling for metabolic measures. No differences were observed between schizophrenia patients with and without a comorbid substance use disorder at baseline. Importantly, the levels of both endocannabinoids significantly decreased after discharge from the emergency setting. Conclusion The current results add to the growing body of evidence of endocannabinoid alterations in schizophrenia. The strong elevation of plasma anandamide levels in schizophrenia patients assessed in the psychiatric emergency setting suggests that anandamide and OEA area potential biomarkers of the psychological turmoil associated with this context.